Prediction of Contrast‐Induced Nephropathy With Persistent Renal Dysfunction and Adverse Long‐term Outcomes in Patients With Acute Myocardial Infarction Using the Mehran Risk Score. Issue 1 (1st October 2012) - Wi, Jin; Ko, Young‐Guk; Shin, Dong‐Ho; Kim, Jung‐Sun; Kim, Byeong‐Keuk; Choi, Donghoon; Ha, Jong‐Won; Hong, Myeong‐Ki; Jang, Yangsoo
Abstract Background: Contrast‐induced nephropathy (CIN) has been generally considered to be transient and associated with unfavorable clinical outcomes. Hypothesis: The aim of this study was to investigate whether Mehran risk score could predict CIN with persistent renal dysfunction and long‐term clinical outcomes in acute myocardial infarction (AMI) patients undergoing percutaneous coronary intervention (PCI). Methods: We analyzed the clinical data of 1041 AMI patients. The primary end point was defined as major adverse cardiovascular and cerebrovascular event (MACCE) including death, reinfarction, target vessel revascularization, heart failure requiring hospital admission, and stroke. Patients were categorized into 4 groups according to risk scores: low (≤ 5, n = 596), moderate (6–10, n = 265), high (11–15, n = 111), and very high (≥16, n = 69). Results: Among the 148 patients (14.2%) who developed CIN, persistent renal dysfunction was observed in 68 patients. Presence in high‐ or very high‐risk groups was the most important independent risk factor of CIN with persistent renal dysfunction (odds ratio: 3.35, 95 confidence interval [CI]: 1.89–5.92, P < 0.001). Furthermore, patients in higher‐risk groups experienced significantly more MACCE and mortality 2 years after PCI. Using multivariate analysis, significant increase in the hazard ratio (HR) for MACCE was noted in moderate‐ (HR: 1.40, 95% CI: 0.97–2.03, P = 0.075), high‐ (HR 1.96, 95% CI: 1.22–3.15, P = 0.006), and very high‐risk (HR 2.40, 95% CI: 1.36–4.21, p = 0.002) groups, compared with the low‐risk group. The very high‐risk group had approximately 6‐fold increase in mortality over the low‐risk group (HR: 6.22, 95% CI: 2.77–13.95, P < 0.001). Conclusions: Mehran risk score predicted CIN with persistent renal dysfunction and long‐term clinical outcomes in patients with AMI. Drs. Jin Wi and Young‐Guk Ko contributed equally to the preparation of the article. This study was supported partly by grants from the Korea Healthcare Technology R&D Project, Ministry for Health, Welfare and Family Affairs, Republic of Korea (No. A085012, A102064, and A110879); the Korea Health 21 R&D Project, Ministry of Health and Welfare, Republic of Korea (No.A08 5136); Yonsei University (6‐2009‐0008); Korea Institute of Medicine; and the Cardiovascular Research Center, Seoul, Korea. The authors have no other funding, financial relationships, or conflicts of interest to disclose.